Anti-Influencer & Peer-To-Peer Marketing: The Shift in Consumer Trust 2026. : JEL Classification: M31, M37, D12, D83, L86 - Harimurti Wulandjani; Supriadi Thalib; Widarto Rachbini; Aryo Seno; Ahmad Fikri (Newinera Publisher, 2026)
This study aims to analyze the effect of anti-influencer and peer-to-peer marketing on purchase intention, with consumer trust as a mediating variable. The phenomenon of increasing consumer skepticism toward influencers, along with the growing reliance on peer-to-peer recommendations, serves as a critical foundation for understanding the shift in trust within digital marketing. This research employs a quantitative approach using a survey method. The population consists of students from the Faculty of Economics and Business, Pancasila University, with a sample of 144 respondents selected through purposive sampling. Data were collected a questionnaire using a Likert scale, and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that anti-influencer has a negative effect on consumer trust and purchase intention, while peer-to-peer marketing has a positive effect on both consumer trust and purchase intention. Furthermore, consumer trust is proven to have a positive effect on purchase intention and acts as a mediating variable in the relationship between peer-to-peer marketing and purchase intention. These findings suggest a shift in consumer trust from influencers toward peer recommendations, which are perceived as more authentic and trustworthy. This study implies that digital marketing strategies should emphasize transparency, authenticity, and the utilization of peer-to-peer communication to enhance trust and marketing effectiveness.